THE ARCHITECT AS DEVELOPER - Portman, John, 1924-2017, author 216281 (New York : McGraw-Hill, 1976)
Has any architect-anywhere-made more of an imprint on the urban scene during the last ten years than John Portman of Atlanta? Starting with his revolutionary Atlanta Regency hotel, whose 23-story lobby attracted worldwide attentions, he has created new kinds of urban environments not only for hotels but in multi-million-dollar downtown developments for San Francisco, Detroit, Los Angeles, and his native Atlanta. Portman is not just an architect for these buildings; in many cases he is the real estate developer as well. His buildings are highly respected as architecture; at the same time he is able to beat the real estate developer at his own game. His projects succeed in the marketplace and have set new standards for hotels, office buildings, merchandise marts, and city center designs.